STRATEGI PENINGKATAN KUALITAS PEMBELAJARAN MATA KULIAH TEORI PENGANGGARAN BERBASIS MATRIK IPA - Siti - Arbainah; Rudi - Handoyono; Lardin - Korawijayanti; Arum Febrianti Ciptaningtyas (Politeknik Negeri Semarang, 2018)
The learning quality improvement model that formulates that the service quality of the learning process influences learning output (GPA), motivates the Managerial Accounting Study Program to improve the quality of service of the learning process in theoretical and practical subjects. Improving the quality of learning services can be done properly if it is known in advance the level of service quality that has been achieved which can be used as a basis for policy making. The subject of budgeting theory is one of the very relevant subjects to formulate a strategy to improve the quality of learning, because the course also contributes in preparing students' supplies to enter the budgeting practicum. Therefore student competency in practical lectures is also determined by the competencies achieved by students in budgeting theory courses. Service quality measured includes five aspects, namely reliability, assurance, responsiveness, empathy and responsiveness. Perception data is obtained through filling out questionnaires with student respondents who take theory and practice budgeting courses in the 2017/2018 academic year, in the Management Accounting Study Program. The collected data is then analyzed by Importance and Performance Analyzes (IPA) and outlined in the IPA matrix. Based on the IPA matrix, strategies can be developed to improve the quality of learning services as expected